High-Fat intake during pregnancy and lactation exacerbates high-fat diet-induced complications in male offspring in mice - Kruse, Michael; Seki, Yoshinori; Vuguin, Patricia M.; Du, Xiu Quan; Fiallo, Ariana; Glenn, Alan S.; Singer, Stephan; Breuhahn, Kai; Katz, Ellen B.; Charron, Maureen J. (Endocrinology, 2013)
Altered fetal environments, such as a high-fat milieu, induce metabolic abnormalities in offspring. Different postnatal environments reveal the predisposition for adult diseases that occur during the fetal period. This study investigates the ability of a maternal high-fat diet (HFD) to program metabolic responses to HFD reexposure in offspring after consuming normal chow for 23 weeks after weaning. Wild-type CD1 females were fed a HFD (H) or control (C) chow during pregnancy and lactation. At 26 weeks of age, offspring were either reexposed (H-C-H) or newly exposed (C-C-H) to the HFD for 19 weeks. Body weight was measured weekly, and glucose and insulin tolerance were measured after 10 and 18 weeks on the HFD. The metabolic profile of offspring on a HFD or C diet during pregnancy and lactation and weaned onto a low-fat diet was similar at 26 weeks. H-C-H offspring gained more weight and developed larger adipocytes after being reintroduced to the HFD later in life than C-C-H. H-C-H mice were glucose and insulin intolerant and showed reduced gene expression of cox6a2 and atp5i in muscle, indicating mitochondrial dysfunction. In adipocytes, the expression of slc2a4, srebf1, and adipoq genes was decreased in H-C-H mice compared with C-C-C, indicating insulin resistance. H-C-H showed extensive hepatosteatosis, accompanied by increased gene expression for cd36 and serpin1, compared with C-C-H. Perinatal exposure to a HFD programs a more deleterious response to a HFD challenge later in life even after an interval of normal diet in mice.
Gesehen am 16.06.2021